COVID-19 prophylaxis with doxycycline and zinc in health care workers: a prospective, randomized, double-blind clinical trial. (September 2022) - Stambouli, Nejla; Driss, Adel; Gargouri, Faten; Bahrini, Khadija; Arfaoui, Bilel; Abid, Rim; Taamallah, Karima; Hannachi, Souha; Boughariou, Sana; Rebai, Aicha; Naas, Imen; Ghanem, Mohamed; et al.
Highlights: Efficacy of doxycycline and zinc as potential treatment of SARS-CoV-2 infection is discussed. SARS-CoV-2 contamination appeared to be reduced after treatment. COVID-19 infection risk was not associated with other comorbidities. The combined treatments of doxycycline and zinc have minimal side effects. ABSTRACT: Objectives: This study aims to assess the efficacy of a combination treatment of doxycycline and zinc in the primary prevention of COVID-19 infection in Tunisian health care workers compared with two control groups. Methods: We conducted a prospective, randomized, double-blind clinical trial over 5 months to determine the efficacy of a preventive combination treatment dose of doxycycline (100 mg/day) and zinc (15 mg/day), compared with a single-dose treatment with doxycycline versus placebo. The effectiveness of preventive treatment was measured by the significant decline in the number of cases of COVID-19 infection and/or a decrease in the viral load as determined by SARS-CoV-2 cycle threshold value using reverse transcription polymerase chain reaction tests. Results: We detected a significant decrease of SARS-CoV-2 infection in the group that received both doxycycline and zinc compared with other participants. We also demonstrated that COVID-19 infection was neither associated with diabetes ( P  = 0.51) nor associated with hypertension ( P  = 0.99), asthma ( P  = 0.52), and chronic obstructive pulmonary disease ( P  = 0.27). Conclusion: Our findings indicated that preventive therapy reduced the risk of SARS-CoV-2. These results suggest that the combination of doxycycline and zinc has a protective effect in patients with SARS-CoV-2 infection.